Analytical Solution for Generating a Wave from a Wall with Changing Temperature. Issue 5 (October 2013) - Takahashi, S.; Sakurai, A.
We consider the problem of wave generation from a wall with changing temperature to analytically solve the linear Boltzmann-BGK equation with diffuse reflection at a wall by successive approximation and to provide a foundation for the numerical approach. Convergence is verified, and approximate solutions used in its proof are utilized to demonstrate its wave-like features observed in the numerical solution.